Branding Strategy of West Java: Fashion Products of The Creative Industry - Popy Rufaidah (AFEBI Management and Business Review, 2017)
In past research, branding strategy application in the creative industry has been left largely unexplored. This study aims to investigate the types of branding strategy elements perceived as the distinctiveness of West Java in fashion products of the creative industry. This study is a cross-sectional study using survey method, which is designed to describe the frequency of customer perceptions of branding strategy elements such as products design, marketing communicationtools and physical environment.  The data used in this study is primary and secondary data. The primary data is obtained from the results of observations, interviews and survey using questionnaires. The respondents of the study are the customers of fashion products in the creative industry who have been living in West Java at lest for two years. The study concludes that there are some critial points in building West Java brand through several branding strategy elements that need more attention such as (i) the performance of blogs and websites as marketing promotional tools used by companies in the creative industry is perceived low (37%); (ii) most of the fashion products marketed by  companies in the creative industry are perceived similar and not unique (57%); (iii) the logo of the fashion products sold in the market by  creative industry players is perceived not attractive (37%) and;  the  places where the fashion products are sold are perceived not clean (46%).Keywords: Branding Strategy, Fashion Products, Creative Industry